Mental Health of Psychiatry Nurses Related with Fatigue, Resilience and Self-Compassion in COVID-19 Pandemic - Ando, Michiyo; Kukihara, Hiroko; Kurihara, Haruka (British Journal of Healthcare and Medical Research, 2022)
Patients and nurses experienced much stress because of infection prevention rule, limitation of meeting families, or going out freely. Then the present study examined 1) the relationships among mental health, mental fatigue, physical fatigue, self-compassion, and resilience, 2) the relationships between mental fatigue and factors of resilience or self-compassion, 3) the most effective factor on mental health of psychiatry nurses in COVID-19 pandemic. Participants were 132 psychiatry nurses at 4 hospitals in Western Japan. They completed questionnaires about mental health by the General Health Questionnaire (GHQ), mental fatigue, physical fatigue, self-compassion, and resilience. The ethical committee permitted this research. Results showed the following. The GHQ related with mental fatigue (r=.70), physical fatigue (r=.54), self-compassion (r= -.50), and Resilience (r= -.40). The GHQ related with “Positivity in nursing (r=-.42)” in resilience factors: positivity in nursing, interpersonal skill, having anchor in personal life, responsivity to novelty. Also the GHQ related with “Over-identification (r=-.35) of self-compassion factors: self-compassion, self-judgment, common humanity, Isolation, mindfulness, and over-identification. From the multiple regression analysis, the mental fatigue was the most effective factor on GHQ (β=.59). These results suggest that mental health related with fatigue, resilience, and self-compassion. Nurses with positivity in nursing and over-identification had high mental health. And mental fatigue was the most effective factor on mental health of psychiatry nurses in COVID-19 pandemic. The intervention to alleviate their mental fatigue will be required.